Effects of pumping profiles on the temperature distributions in doubleend pumped solid-state lasers: A comparison study - Hind Jawad; Mohammed AbdulRazzaq; Khalid Shibib (Engineering and Technology Journal, 2022)
In this work, the effects of pumping profiles on the temperature distributions in solid-state lasers pumped by laser diode from two different end faces were studied. With different pump spot radii of , various exponent factors were examined to evaluate the behavior of temperature distributions due to Gaussian and super-Gaussian profiles. For a Gaussian pumping (n=2), the maximum temperature difference on each rod face was calculated to be  295.5 K and 226 K, respectively, at a total pump power of  92.8 W (46.4 W per face). While at the same pumping power, the temperature decreased as the n exponent increased. A good match was obtained between the proposed model and the previous works listed in the literature.